(untitled) (Texas Journal of Philology, Culture and History, 2024)
The article talks about using novels to teach and learn Russian as a foreign language and how it helps with reading comprehension. It also claims that most new students have a strong interest in games, music, fairy tales, and role plays. The needs should guide teachers’ work. The interests of the students, as well as needing to come up with fresh, entertaining ideas for engaging classes. Students’ speaking and listening abilities can be developed as well as their reading comprehension by using novels. By encouraging new students to learn Russian by romance reading from an early age, you can pique their interest and raise their awareness of the language’s usage.